2018
DOI: 10.3126/ije.v6i4.18910
|View full text |Cite
|
Sign up to set email alerts
|

Quality Assessment of Ground Water in Dhamar City, Yemen

Abstract: Chemical and statistical regression analysis on groundwater at five fields (17 sampling wells) located in Dhamar city, the central highlands of Yemen, was carried out. Samples were collected from the ground water supplies (tube wells) during the year 2015. Physical parameters studied include (values between bracket s represents the measured mean values) temperature (T, 25°), total dissolved solids (TDS, 271.47), pH (7.5), and electrical conductivity (EC, 424.18). The chemical parameters investigated include to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 9 publications
2
2
2
Order By: Relevance
“…Also this result is low compared to the result obtained by [44] which was 479.64 mg/l. On the other hand, the result obtained in the current study is lower than the obtained by [33] on the groundwater in Zabid city, Yemen, SO 4 2mean was 143 mg/l, and a study carried out by [31] on the groundwater Dhamar city Yemen, was SO 4 2mean SO 4 2-61.03 mg/l.…”
Section: Sulfate (So4 2-)contrasting
confidence: 93%
See 3 more Smart Citations
“…Also this result is low compared to the result obtained by [44] which was 479.64 mg/l. On the other hand, the result obtained in the current study is lower than the obtained by [33] on the groundwater in Zabid city, Yemen, SO 4 2mean was 143 mg/l, and a study carried out by [31] on the groundwater Dhamar city Yemen, was SO 4 2mean SO 4 2-61.03 mg/l.…”
Section: Sulfate (So4 2-)contrasting
confidence: 93%
“…Also There is strong positive correlation between TH and cations Ca 2+ (0.918**), Mg 2+ (0.946**) and fe 2+ (0.547*) and with NO 3 -(0.527*). This result is agrees with similar results obtained by [31]. Positive correlation between hardness and each of Ca 2+ and Mg 2+ is because of their importance in hardness of water.…”
Section: Fecal Coliform (Fc)supporting
confidence: 93%
See 2 more Smart Citations
“…The technology use to manage the sewage wastewater is dependent on the life style of the residents and the climatic conditions of the sewage WSP. Life style of residents affects the type of wastes and climate affects the natural and biological processes associated with phytoremediation that occur to treat wastes (Aizari et al, 2017). Abdedi and Najafi (2001) showed that wastewater is reused in agriculture and the practice has benefits (Nadafi et al, 2005).…”
mentioning
confidence: 99%